Rachunek kosztów działań oparty na czasie - Bojnowska, Agnieszka (Time-Driven Activity Based Costing, 2005)
The interest in acticity based costing has brought a lot of descriptions in literature and many practical applications in companies. However, while it was being discussed and used, some disadvantages of this model have been found. They are the results of assumptions of this conception and caused by external factors of economical surroundings. The aim of this article is to present the weaknesses of standard activity based costing, some reasons of their appearance and their consequences in process of practical aplication and to show the idea of time driven activity based costing - assumptions and steps of allocating costs. This new approach, proposed by the authors of standard ABC, enables faster and cheaper implementation, larger usage and easier updating the model. It provides the increase of utility and at the same time it maintains high accuracy of the costs allocation.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 67-78